High-Resolution Microscopic Images of Mosquito Vectors (Diptera: Culicidae): Proper Identification of Culex and Aedes during Dengue Outbreak Situation in Bangladesh - Yesmin, Farzana; Hasan, Md. Fahad; Hossain, Tahera; Akter, Shamme; Uddin, Md Nazim; Md. Hasanuzzaman (HAYATI Journal of Biosciences, 2025)
High-resolution microscopic images of the 8th abdominal segment, comb scales, pectin, tuft of hairs, saddle, head antenna, thoracic hooks and other morphological characteristics of Culex quinquefasciatus, Aedes aegypti and Aedes albopictus have been provided for the first time in Bangladesh. Mosquitoes spread deadly diseases (dengue, chikungunya, Japanese encephalitis, yellow fever, malaria, filariasis) that kill millions of people every year including Bangladesh. During dengue and dengue outbreak situations, it is very much necessary to identify the dengue-occurring mosquito vectors. Proper identification of the mosquito vectors of Bangladesh is the key factor for public health protection and disease prevention. Larval movement patterns and habitat characterization were also observed. Results obtained in this study revealed that dengue virus can also be carried by other Aedes species rather than A. aegypti. Results were discussed with previous study dealing with Aedes mosquito samples of Bangladesh. The findings will be very useful for the proper identification of dengue mosquito vectors in Bangladesh and the knowledge assists in the accuracy of mosquito control activities as well as prevention of mosquito-borne diseases.